Suspended Organic Removal by Electrocoagulation Process - Firra Rosariawari; Iwan Wahjudianto; Tuhu Agung Rachmanto (Future Science)
Electrocoagulation is an electrolysis process with the aimed of destabilizing suspensions, emulsions, and solutions containing contaminants. The process was to connect the direct current (DC) through the water to become flok that it was easily separated. This electrocoagulation process required an electrolyte solution and an electrode. Batik wastewater was used as an electrolyte solution and Aluminium as the electrode. The mechanism of the coagulation process for reducing organic suspension was, on an electrolyte in this case was batik wastewater placed two Aluminium electrodes (cathode and anode) and connect it to the direct current, so it’s called electrochemical process. This research aimed to treat wastewater batik by using electrocoagulation process in eliminating of suspended organic. This was due to the fact that wastewater was generally alkaline and has high organic matter and high suspended solids. Suspended solid produced in the process of preparation. Based on the electrocoagulation process, the treatment variables in this research are, variations of current strength are 1, 2, 3, 4 and 5 Ampere and contact time are 60,90,120,150 and 180 minutes. While other influential factors were as a fixed variable. The specified variables were the thickness of the plate and the distance between the plate, the temperature according to the ambient temperature. In this research, the optimum removal of Tss and COD at the largest electric current was 5 A and at 180 minutes of detention time. Removal percentage of Tss reached 94.87% while COD removal reached 93.19%.